2021
DOI: 10.15294/abdimas.v25i2.34828
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Pengetahuan Peserta Training of Trainer (ToT) “Pelatihan Batik dengan Pewarnaan Alami” dengan Penyuluhan Mengenai Pengolahan Limbah Cair Industri Batik

Abstract: Batik tulis merupakan salah satu warisan kesenian tradisional budaya Indonesia, khususnya bagi Daerah Istimewa Yogyakarta yang sejak tahun 2014 ditetapkan sebagai Kota Batik Dunia oleh World Craft Council. Namun, eksistensi batik tulis pelan-pelan tergeser seiring dengan perkembangan teknologi yang menyebabkan semakin maraknya produksi batik cap dan batik cetak sehingga minat generasi muda terhadap batik tulis menurun. Untuk meningkatkan minat dan motivasi generasi penerus agar lebih mengenal batik dan proses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Materials and equipment introduced include wax, dyes, fabrics, boilers, pans, stirrers, stamp pads, and canting. This increase is under the results of previous activities (Hakika et al, 2021), which showed that increased knowledge about batik could increase after training. b.…”
Section: Resultssupporting
confidence: 71%
“…Materials and equipment introduced include wax, dyes, fabrics, boilers, pans, stirrers, stamp pads, and canting. This increase is under the results of previous activities (Hakika et al, 2021), which showed that increased knowledge about batik could increase after training. b.…”
Section: Resultssupporting
confidence: 71%